Keeping the human in the loop: are autonomous decisions inevitable? - Pöhler Jonas; Flegel Nadine; Mentler Tilo; Van Laerhoven Kristof (i-com)
Control rooms play a crucial role in monitoring and managing safety-critical systems, such as power grids, emergency response, and transportation networks. As these systems become increasingly complex and generate more data, the role of human operators is evolving amid growing reliance on automation and autonomous decision-making. This paper explores the balance between leveraging automation for efficiency and preserving human intuition and ethical judgment, particularly in high-stakes scenarios. Through an analysis of control room trends, operator attitudes, and models of human-computer collaboration, this paper highlights the benefits and challenges of automation, including risks of deskilling, automation bias, and accountability. The paper advocates for a hybrid approach of collaborative autonomy, where humans and systems work in partnership to ensure transparency, trust, and adaptability.